Digital Transformation in MSMEs in Indonesia: The Importance of Commitment to Change - Wahyono, Tekad (International Journal of Social Service and Research, 2024)
The current landscape of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia faces a critical challenge in the form of digital transformation, necessitating a unified commitment from all organizational stakeholders. This research endeavors to explore the pivotal role of commitment to change in facilitating digital transformation within Indonesian MSMEs. By scrutinizing existing literature and delineating the positive outcomes associated with commitment to change, this study aims to unearth key factors influencing the successful implementation of digital transformation initiatives in MSMEs. Employing a combination of case study and survey methodologies, our research seeks to not only enhance theoretical insights but also contribute practical understandings to support MSMEs in their pursuit of digital transformation. Through an in-depth analysis, this study aspires to provide strategic recommendations that can guide MSMEs toward effective and sustainable digital transformation. Ultimately, this research contributes to the broader discourse on organizational change and digitalization, offering valuable insights for policymakers, academics, and practitioners alike.